A novel method to assist gastric tube insertion: a case series. Issue 8 (17th June 2010) - Harvey, Martyn; Cave, Grant
Abstract : Gastric tube insertion in the intubated patient can prove both difficult and frustrating. A simple modification to the standard gastric tube and corresponding technique of insertion is described which enables directional manoeuvring of the tube tip. Experience with the technique is described in a case series of 10 patients.